Belief in Conspiracy Theories and Susceptibility to the Conjunction Fallacy - Brotherton, Robert; French, Christopher C. (Applied cognitive psychology, 2014)
Summary People who believe in the paranormal have been found to be particularly susceptible to the conjunction fallacy. The present research examines whether the same is true of people who endorse conspiracy theories. Two studies examined the association between conspiracist ideation and the number of conjunction violations made in a variety of contexts (neutral, paranormal and conspiracy). Study 1 found that participants who endorsed a range of popular conspiracy theories more strongly also made more conjunction errors than participants with weaker conspiracism, regardless of the contextual framing of the conjunction. Study 2, using an independent sample and a generic measure of conspiracist ideation, replicated the finding that conspiracy belief is associated with domain‐general susceptibility to the conjunction fallacy. The findings are discussed in relation to the association between conspiracism and other anomalous beliefs, the representativeness heuristic and the tendency to infer underlying causal relationships connecting ostensibly unrelated events. © 2014 The Authors. Applied Cognitive Psychology Published by John Wiley & Sons Ltd.